Language-Based Testing for Pushdown Reactive Systems - Bonifacio, Adilson Luiz (Anais do Simpósio Brasileiro de Métodos Formais (SBMF), 2023)
Testing reactive systems is important to guarantee a precise and robust software development process. Pushdown reactive systems are complex applications where the interaction with the environment is regulated by a pushdown memory and, in general, can be specified by the formalism of Input/Output Visibly Pushdown Labeled Transition System (IOVPTS). A conformance checking can then be applied to verify whether an implementation is in compliance to a specification using an appropriate conformance relation. In this work, we establish a conformance relation based on Visibly Pushdown Languages (VPLs) to model sets of desirable and undesirable behaviors of systems. Further, we show that test suites with a complete fault coverage can be generated using this new conformance relation for pushdown reactive systems.